Understanding the general instruction of the Roman missal - Moore, Gerard, 1956- (New York : Paulist Press, 2007)
"Dr. Moore's clearly written book is an exploration and commentary on the inner dynamics and theological streams at the heart of the General Instruction of the Roman Missal (GIRM), which is the core text for celebrating the Mass."--BOOK JACKET.
Principles of interpretation -- Theological themes -- The mystery of the church -- The people of god arrayed hierarchically -- The eucharistic celebration.
Includes bibliographical references.
Keywords: Catholic Church -- Liturgy -- Texts; Missals